The surgical safety checklist: a quantitative study on attitudes and barriers among gynecological surgery teams - Junming Gong; Yushan Ma; Yunfei An; Qi Yuan; Yun Li; Juan Hu (BMC, 2021)
Abstract Background Implementation of the surgical safety checklist (SSC) plays a significant role in improving surgical patient safety, but levels of compliance to a SSC implementation by surgical team members vary significantly. We aimed to investigate the factors affecting satisfaction levels of gynecologists, anesthesiologists, and operating room registered nurses (OR-RNs) with SSC implementation. Methods We conducted a survey based on 267 questionnaires completed by 85 gynecologists from 14 gynecological surgery teams, 86 anesthesiologists, and 96 OR-RNs at a hospital in China from March 3 to March 16, 2020. The self-reported questionnaire was used to collect respondent's demographic information, levels of satisfaction with overall implementation of the SSC and its implementation in each of the three phases of a surgery, namely sign-in, time-out, and sign-out, and reasons for not giving a satisfaction score of 10 to its implementation in all phases. Results The subjective ratings regarding the overall implementation of the SSC between the surgical team members were different significantly. "Too many operations to check" was the primary factor causing gynecologists and anesthesiologists not to assign a score of 10 to sign-in implementation. The OR-RNs gave the lowest score to time-out implementation and 82 (85.42%) did not assign a score of 10 to it. "Surgeon is eager to start for surgery" was recognized as a major factor ranking first by OR-RNs and ranking second by anesthesiologists, and 57 (69.51%) OR-RNs chose "Too many operations to check" as the reason for not giving a score of 10 to time-out implementation. "No one initiates" and "Surgeon is not present for 'sign out'" were commonly cited as the reasons for not assigning a score of 10 to sign-out implementation. Conclusion Factors affecting satisfaction with SSC implementation were various. These factors might be essentially related to heavy workloads and lack of ability about SSC implementation. It is advisable to reduce surgical team members' excessive workloads and enhance their understanding of importance of SSC implementation, thereby improving surgical team members' satisfaction with SSC implementation and facilitating compliance of SSC completion.